Cost-effectiveness of dapagliflozin versus DPP-4 inhibitors as an add-on to Metformin in the Treatment of Type 2 Diabetes Mellitus from a UK Healthcare System Perspective. Issue 1 (June 2015) - Charokopou, M.; McEwan, P.; Lister, S.; Callan, L.; Bergenheim, K.; Tolley, K.; Postema, R.; Townsend, R.; Roudaut, M.
Abstract Background Type 2 diabetes mellitus (T2DM) is a chronic, progressive condition where the primary treatment goal is to maintain control of glycated haemoglobin (HbA1c). In order for healthcare decision makers to ensure patients receive the highest standard of care within the available budget, the clinical benefits of each treatment option must be balanced against the economic consequences. The aim of this study was to assess the cost-effectiveness of dapagliflozin, the first-in-class sodium-glucose co-transporter 2 (SGLT2) inhibitor, compared with a dipeptidyl peptidase-4 inhibitor (DPP-4i), when added to metformin for the treatment of patients with T2DM inadequately controlled on metformin alone. Methods The previously published and validated Cardiff diabetes model was used as the basis for this economic evaluation, with treatment effect parameters sourced from a systematic review and network meta-analysis. Costs, derived from a UK healthcare system perspective, and quality-adjusted life years (QALYs), were used to present the final outcome as an incremental cost-effectiveness ratio (ICER) over a lifetime horizon. Univariate and probabilistic sensitivity analyses (PSA) were carried out to assess uncertainty in the model results. Results Compared with DPP-4i, dapagliflozin was associated with a mean incremental benefit of 0.032 QALYs (95 % confidence interval [CI]: −0.022, 0.140) and with an incremental cost of £216 (95 % CI: £-258, £795). This resulted in an ICER point estimate of £6, 761 per QALY gained. Sensitivity analysis determined incremental costs to be insensitive to variation in most parameters, with only the treatment effect on weight having a notable impact on the incremental QALYs; however, there were no scenarios which raised the ICER above £15, 000 per QALY. The PSA estimated that dapagliflozin had an 85 % probability of being cost-effective at a willingness-to-pay threshold of £20, 000 per QALY gained. Conclusions Dapagliflozin in combination with metformin was shown to be a cost-effective treatment option from a UK healthcare system perspective for patients with T2DM who are inadequately controlled on metformin alone.